Hubungan Pola Asuh Orang Tua Dan Lingkungan Dengan Perilaku Verbal Abuse Pada Anak Prasekolah - Harkomah, Isti (Universitas Fort De Kock Bukittinggi, 2020)
Background : Verbal abuse is called emotional child abuse, verbal acts or behaviors that have adverse emotional consequences. without realizing it, parents every day verbal abuse their children. This form of Verbal Abuse is generally done by threatening, criticizing, yelling, isolating the child, giving the child a negative nickname or making fun of him. This behavior influences the parenting styles given to children. Parenting is the ability of parents to provide time, attention and support for their children so that they can grow and develop physically, mentally and socially. Aim : The purpose of this study was to determine the relationship between parenting styles and the environment with Verbal Abuse Behavior in Preschool Children in Simpang III Sipin Village, Jambi City. Method : This research method is a descriptive quantitative study with a cross sectional design. The technique of determining the place of this research is proportional technique. Sampling uses a total sampling technique with a total sample of 54 people. Data were collected using a questionnaire, the data that had been collected were analyzed by univariate and bivariate. The analysis in this study used chi-square. Results : The results showed that parenting style and the environment were significantly related to verbal abuse behavior with a P-Value <0.05.Keywords: Parenting, Environment, Verbal Abuse